Experiment Study on Dynamic Effects of Tower-Line Systems Induced by Ice Shedding - Xianzhong Xie; Yuanjie Wu; Kaiyuan Liang; Sai Liu; Jian Peng (Advances in Civil Engineering)
Taking the 220 kV transmission line as the prototype, a test model of the double-span tower-line system with a scale ratio of 1 : 20 was proposed on the basis of dynamic similarity theory. 14 different working conditions including zippered, simultaneous, entire, and local ice-shedding were controlled and realized by use of the program-controlled mode. The displacement transient responses of transmission line under these ice-shedding conditions were analyzed in detail. The results show that the variation laws of the ice-shedding dynamic-load coefficient and the jump height with the velocity, quantity, and position of the ice-shedding are obtained, which can provide references for the design of the transmission tower-line system.